2006
DOI: 10.1038/sj.bjc.6603247
|View full text |Cite
|
Sign up to set email alerts
|

Incidence trends of prostate cancer in East Anglia, before and during the era of PSA diagnostic testing

Abstract: We investigated prostate cancer incidence in East Anglia from 1971 to 2000. Using age-period-cohort modelling, the number of cases expected in 1991–2000, based on pre-PSA trends, 1971–1990, was compared with that observed. Based on pre-1991 trends, 9203 new cases were expected in 1991–2000, but 9788 cases were observed, an excess of 6%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The relatively small percentage of prostate cancer cases, 5.6% (38 out of 680), between 1996 and 2002 with a recorded prediagnosis or peridiagnosis PSA test is surprising. However, the estimated number of excess cases (252) in East Anglia based on the results here is very close to the number estimated (289) based on age-period-cohort analysis reported in our previous study (Pashayan et al, 2006). There may be minor faults in record linkage between the cancer registry and the laboratory records for PSA testing and subsequent underestimation in the estimates of excess diagnosis associated with PSA testing.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The relatively small percentage of prostate cancer cases, 5.6% (38 out of 680), between 1996 and 2002 with a recorded prediagnosis or peridiagnosis PSA test is surprising. However, the estimated number of excess cases (252) in East Anglia based on the results here is very close to the number estimated (289) based on age-period-cohort analysis reported in our previous study (Pashayan et al, 2006). There may be minor faults in record linkage between the cancer registry and the laboratory records for PSA testing and subsequent underestimation in the estimates of excess diagnosis associated with PSA testing.…”
Section: Discussionsupporting
confidence: 84%
“…A descriptive epidemiological study in East Anglia has shown a 6% excess of prostate cancer registrations during 1991 -2000 relative to expectations based on pre-1991 trends, coincident with an increase in prostate-specific antigen (PSA) testing (Pashayan et al, 2006). This increase in PSA testing came not from a formal screening programme (no such programme existed), but rather from the increased use of the test for case finding and in the investigation of men with urological symptoms.…”
mentioning
confidence: 99%
“…Indeed, prostate cancer accounts for over a quarter of all cancers in men and the risk increases with age (1). There has been an increase in the reported incidence of prostate cancer since the early 1980's, most likely due to an increased use of screening using the PSA test (31) although the effectiveness of screening for prostate cancer remains controversial (32). …”
Section: Discussionmentioning
confidence: 99%
“…An argument against PSA testing explaining all of the increases in prostate cancer incidence is that the rates were already increasing in countries such as the USA and Aus- tralia prior to the introduction of PSA testing [48]. Moreover, increases have been observed in countries with a lower prevalence of PSA testing, such as Japan (Fig.…”
Section: Trendsmentioning
confidence: 97%